Fake news about the COVID-19 pandemic: perception of health professionals and their families - Mayckel da Silva Barreto; Carolina da Silva Caram; José Luís Guedes dos Santos; Rebeca Rosa de Souza; Herbert Leopoldo de Freitas Goes; Sonia Silva Marcon (SciELO, 2021)
ABSTRACT Objective: To know the perception of health professionals and their families about fake news related to the COVID-19 pandemic. Method: Descriptive-exploratory study with a qualitative approach. Twenty-eight individuals participated, including seven physicians, seven nurses, and 14 family members. Data collection took place between August and October 2020, with audio-recorded interviews. After transcription, the content was analyzed using Content Analysis, thematic modality. Results: Three categories were identified: "Context of the occurrence and dissemination of fake news in times of pandemic"; "Consequences of fake news on the experience of the pandemic"; and "Coping strategies to contain/combat fake news". Conclusion: Sociocultural, political, educational, and technological aspects influence the occurrence and dissemination of fake news, which have consequences such as: misinformation, self-medication, worsening in the professional-patient relationship, increased need for additional research, and fear in the population. To face the current situation, greater control by the State is required, with investigation and punishment of people who disseminate fake news, as well as greater awareness among the population on the subject.